PENGEMBANGAN PARIWISATA BERBASIS ECOTOURISM DI SITU GUNUNG SUKABUMI - Sukmamedian, Haufi (JURNAL MANAJEMEN KULINER, 2022)
Ecotourism is a tourist trip to an environment, both natural and artificial, as well as existing culture, which is informative and participatory, which aims to ensure the preservation of nature and socio-culture. So, ecotourism activities directly provide access for everyone to see, know, and enjoy the natural, intellectual and cultural experiences of the local community. This research is quantitative descriptive research with tools or instruments to measure, among others: observation, documentation, interviews and questionnaires. This research uses Important Performance Analysis, Customer Satisfaction Analysis and SWOT Analysis methods which are tools to assess the level of importance and performance of Situ Gunung attractions, visitor satisfaction with the performance of Situ Gunung managers and the formulation of development strategies for Situ Gunung managers, then the average value The average level was analyzed on the Importance-Performance Matrix, Customer Satisfaction analysis and SWOT sample and the population is Situ Gunung visitors.